The interface between Western mental health care and indigenous healing in South Africa: Xhosa psychiatric nurses' views on traditional healers - Kahn, Marc Simon (Rhodes University, Faculty of Humanities, Department of Psychology, 1996)
Xhosa psychiatric nurses stand unique at the interface between Western mental health care and indigenous healing in South Africa. They stem from a cultural history that is embedded within traditional health care discourses and yet are trained and work within a Western psychiatric model. In embodying the intersection between these two paradigms, they are faced with the challenge of making sense of such an amalgamation. These nurses' views are thus valuable in reflecting this intersection and illustrating many of the central concerns that surround it. This study explicates the views of these nurses toward traditional healers and their potential role in mental health care in South Africa. In addition, it illuminates some of the cultural dynamics at work amongst these subjects as they struggle to make sense of their unique cultural position. Using a questionnaire-based methodology, the views of Xhosa psychiatric nurses in a psychiatric hospital in the Eastern Cape, toward traditional healers and their role in mental-health care, were examined. The findings reveal that the vast majority of these nurses believe in traditional cosmology, involve themselves in traditional ritual practices and regularly visit traditional healers as patients. In suggesting ways in which indigenous healing and Western mental health care can work together, 75% of the nurses were in favour of a general referral system between the hospital and traditional healers, most (77%) agreed that certain patients would be better off being treated by both the hospital and traditional healers than they would if they were only being treated by the hospital alone, and 85% of the subjects agreed that patients who are already seeing traditional healers should check if psychiatric medication might help them. These findings indicate that these nurses operate across two healing systems which are at this point not conceptually compatible. This results in deep cultural tension for the nurses. In being entangled in the dialectical tension created in this context, the nurses manage the incongruencies in three general ways: a) Most, in one form or another, incorporate beliefs from both systems into an integrative model, b) some assimilate their cultural belief system into the Western mental health paradigm, throwing off their beliefs in traditional healing, and c) others remain ambivalent in the dialectic between traditional and Western health care discourses. Although this may suggest that these nurses reside within a cultural milieu that is somewhat unhealthy, at another level, in managing and containing the incompatibility between the two systems, these nurses ensure a space for on-going and healthy critique of the underlying assumptions involved in this health care malaise.
Keywords: Mental health services -- Research -- South Africa; Traditional medicine -- South Africa; Black people -- Mental health -- South Africa; Mental health -- South Africa